Assistance with Packaging and Marketing of Creative Hand ProductsSome people in Tete Batu Selatan Village, especially Otak Bangket Hamlet, have creative handmade products that have difficulty in packaging and marketing. Even though the village government has provided sufficient support such as MSME training and product outreach to visitors, these two things have not been able to increase visitors' purchasing power and of course the local community's income. This community service aims to assist - Muhammad Aminuddin; Yusron; Annisa Saputri; Baiq Oktavia Ningrat; Istiqomah (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2024)
Some people in Tete Batu Selatan Village, especially Otak Bangket Hamlet, have creative handmade products that have difficulty in packaging and marketing. Even though the village government has provided sufficient support such as MSME training and product outreach to visitors, these two things have not been able to increase visitors' purchasing power and of course the local community's income. This community service aims to assist the community to package and market their products with modern packaging and digital-based marketing. The implication of this assistance is that, little by little, people are starting to realize the importance of attractive packaging and the use of social media as a place to market their products. So, with this packaging and marketing strategy, many visitors are interested in buying their creative products from low to high prices.